Control interno del departamento de cobranza de la Cooperativa San Antonio C.A. Ltda. sucursal La Unión - Suarez Silva, Marlon Emilio (2021)
This case study is focused on Internal Control of the Collection Department of the Cooperativa San Antonio C.A. Ltda. Sucursal La Unión will help to take into account the different processes that are carried out within the collection department with the sole purpose of correctly establishing the types of deficiencies that are found within the internal control of said department, carefully analyzing all and each of the characteristics of the client at the time of granting loans, taking into account the means they have to not be late with their payments and thus also the implementation of assistance so that they make a correct investment. Contributing in this way not only to the growth of the entity, but also to that of the client, for this, credit policies must be taken into account as well as those of existing collections within the entity, if applicable, it must be considered the overdue portfolios based on them to apply the solutions or look for alternatives considering the clients who are in default and be able to classify them.